Etiology of acute gastroenteritis among children less than 5 years of age in Bucaramanga, Colombia: A case-control study - Farfán-García, Ana E.; Imdad, Aamer; Zhang, Chengxian; Arias-Guerrero, Mónica Y.; Sánchez-Álvarez, Nayibe T.; Iqbal, Junaid; Hernández-Gamboa, Adriana E.; Slaughter, James C.; Gómez-Duarte, Oscar G. (PLOS Neglected Tropical Diseases, 2020)
Author summary Acute gastroenteritis (AGE) is a leading cause of mortality in children under 5 years of age in low- and middle-income countries (LMIC). The highest burden of AGE disease is concentrated in tropical areas where populations lack access to clean water, adequate sanitation and hygiene, making this condition a neglected disease. Limited information on etiology, associated malnutrition, and mortality among underserved communities makes difficult the development of strategies for AGE prevention and treatment. This case-control study among children less than 5 years of age in Bucaramanga, Colombia, revealed that viral followed by bacterial organisms explained the larger proportion of AGE, being norovirus the most common organism. The higher rate of infections and co-infections among cases compared to controls was associated with AGE. This study also reports the identification of three new E. coli pathotypes among cases designated as biofilm-forming enteroinvasive E. coli (BF-EIEC), enteroaggregative/enteropathogenic E. coli, and enteroaggregative/enterotoxigenic E. coli (EAEC/ETEC).